Needs analysis of an augmented reality-based picture story module to improve social awareness and reading literacy among elementary school students - Abdulah, Abdulah (Priviet Social Sciences Journal, 2025)
This study aimed to reveal students' needs for Augmented Reality-based picture story modules to improve reading literacy and social awareness. The subjects of this study were 30 fifth-grade students from SD S Muhammadiyah Sungailiat. Data collection techniques included interviews, observations, questionnaires, and documentation. Qualitative research data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. Quantitative data from the needs questionnaire were analyzed using a percentage formula to determine the level of students' needs for AR-based picture story modules. Furthermore, to maintain data validity, this study used source and technical triangulation techniques. The results of this study indicate that the need for AR-based picture story modules is high. The percentage range of needs for Augmented Reality-based picture story modules is at 73.33% - 87.50%. These findings are seen in each indicator, namely the reading interest indicator and picture stories, which obtained a percentage of 86.67%. This percentage indicates the category of "very needed." The indicator of difficulties and weaknesses in current learning obtained a percentage of 73.33%. This percentage is in the category of "needed." The indicator of the need for a new learning module obtained a percentage of 83.61%. This result is classified as the category of "very needed." The indicator of student acceptance and interest in AR obtained a percentage of 87.50%. This indicator category is "very needed." This is an indicator of the need for module features. The results of the analysis of this indicator showed a percentage of 85.67%. This indicator is in the category of "very needed." Based on these findings, it can be concluded that students need an AR-based picture story module that can make learning activities more interactive, interesting, and meaningful. AR-based modules can be designed to improve reading literacy and social awareness of students. This research serves as the basis for the development of an Augmented Reality-based picture story module in the next research stage.